2021
DOI: 10.3390/su13105634
|View full text |Cite
|
Sign up to set email alerts
|

Income Heterogeneity and the Environmental Kuznets Curve Turning Points: Evidence from Africa

Abstract: The concept of environmental sustainability aims to achieve economic development while achieving a sustainable environment. The inverted U-shape relationship between economic growth and environmental quality, also called Environmental Kuznets Curve (EKC), describes the correlation between economic growth and carbon emissions. This study assesses the role of agriculture and energy-related variables while evaluating the EKC threshold in 54 African economies, and income groups, according to World Bank categorizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…The reason may be that the differences in the regional economic development levels were not considered when examining the EKC effect of county carbon emissions. However, related studies showed that income heterogeneity was also an important factor affecting the establishment of the EKC [ 70 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The reason may be that the differences in the regional economic development levels were not considered when examining the EKC effect of county carbon emissions. However, related studies showed that income heterogeneity was also an important factor affecting the establishment of the EKC [ 70 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, empirical analyses of the applicability of the carbon emission EKC in different income countries produced mixed conclusions. For example, Ogundipe et al supported the establishment of the EKC hypothesis only in a low-income group in Africa [ 72 ], Azam et al recognized the existence of the EKC effect only in low-income and low-middle-income countries [ 73 ], and Tachega et al found that the EKC hypothesis was effective only in the samples of low-income, middle-income and upper-middle income economies in Africa [ 74 ]. There is also empirical evidence from different industries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the most common is once again the analysis of the influence that certain variables, including GDP, have on emissions. The relationship between emissions, GDP, and energy consumption has also been studied in different scenarios [39] and in different countries: in 54 African countries [40], in 17 countries in Europe and Asia [41], and in 30 Chinese provinces [42]. The results show that non-renewable energies have a positive causality on CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%